Dialectic of “pleasure and suffering”: the relationship of master’s and doctoral students with their academic work - Salgado, Camila Cristina Rodrigues; Aires, Renan Felinto de Farias; Dos Santos, Fernanda Julyanna Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
The work relationship within society shows itself as a fundamental element by means of which man is structured psychologically and may result in pleasure and/or suffering, which is an object of study for the psychodynamics of work. In this field, a gap is noticed in exploring the pleasure-suffering dialectic within the academic scenario regarding the comparison between master’s and doctoral students. This study aims to understand the subjectivity in the pleasure and suffering relationships of administration masters’ and doctoral students with their academic work. For this, focused interviews were carried out and then coded and analyzed qualitatively by means of content analysis. As a result, the masters’ students were observed to point at the feeling of displeasure as the source of suffering and at professional growth as the source of pleasure. Doctoral students, in turn, also indicated displeasure as the source of suffering, but interpersonal relationships at work stood out as the source of pleasure.